QUALITY ASSURANCE IN UNDERGRADUATE MEDICAL EDUCATION: THE BANGLADESH EXPERIENCE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: The third wave of quality has now penetrated the higher education sector, including medical education. Due to its unique characteristics, i.e. its closed link with health services and medical practices, quality assurance in undergraduate medical education needs its own model. However, recent literature review has shown that research on this area has been lacking. This study attempted to learn inductively from the experience of a country who has implemented this scheme, nationally and at the institutional level. Methods: This study is conducted under the qualitative paradigm using case study as the methodology approach, because the main aim of this study is to describe the experience of a particular setting. Data collection methods include documents, qualitative interviews with key informants and observation.To analyse the data, day's method has been applied, comprising of the following steps: describing, classifying, connecting, and creating an account in the end. Result and conclusions: The description of the phenomena, i.e. quality assurance in undergraduate medical education, is divided into processes, strategies and scheme. The process describes the dynamics in developing the scheme. The strategy describes how the scheme is adopted. The scheme explains the actual scheme that has come up through the process and the strategy. Lessons learnt from this case show that leadership, decision making, agent of change, external pressures, adopters and rejects influence the implementation effectiveness of such scheme.